Udział przedsiębiorstw żydowskich w przemyśle włókienniczym Łodzi w latach 1860-1914 - Ziomek, Wojciech (Acta Universitatis Lodziensis. Folia Historica, 1998)
An issue concerning participation of Jewish firms in textile industry of Łódź has not been clearly explained till now. The rate of participation of Jewish firms is often regarded as smaller than German ones. There is no monography concerning Jews of Łódź in 1860-1914, which would enable us to broaden our knowledge of that community and its importance for city history. Between 1885 and 1887 a serious press debates took place. On the one hand, legal acts, which were expected to limit rights of Jews were demanded. On the other hand, Jews were supported by authors who showed their importance for economic development of the Kingdom of Poland. The rate of participation of Jewish firms in textile industry of Łódź was small at first (about 11% of total value of production), but constantly increased and on the eve of the XXth century exceeded 45%. To 1914 it was stabilized on a level of 40% of total value of production. Jewish factories were quickly mechanized and were regarded as the most up to date in Łódź. Their dynamics of economic growth considerably exceeded an average development of Łódź industry. It must be said, Jewish industrialists played an important part in creating textile industry of Łódź, however, they were often discriminated. As well they were supported by many Polish business activists and economists who appreciated their importance for economy of the Kingdom of Poland.